Pengaruh Model Team Game Tournament (Tgt) Terhadap Kemampuan Berpikir Kritis Pada Mata Pelajaran Matematika Kelas 3 Sd - Yana, Mei; Dewi, Galuh Kartika; Mubarok, M. Khusni (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
The problem identified in this study is that the teacher still used a lecture and question answer method that is one-way in nature. This approach resulted in low student participation, limited interaction, and shallow conceptual understanding. The study employed an experimental research design with an experimental group taught using the Teams Games Tournament (TGT) learning model and a control group that received conventional direct instruction. The findings showed that the control group’s average pretest score was 30.4%, increasing to 62% in the posttest. Meanwhile, the experimental group’s average pretest score of 30.8% rose to 79.2%. Compared to the control group, the experimental group achieved significantly higher gains. Students’ critical thinking skills in the two groups differed markedly after treatment. The Mann Whitney test yielded a significance value of p = 0.001 (p < 0.05), indicating a statistically significant difference. Furthermore, the critical thinking activity questionnaire showed an actual score of 704 out of 1,000, or 70.4% achievement, placing students in the good category of critical thinking ability. Overall, the TGT model had a significant positive impact on enhancing students’ critical thinking skills.